Detection of immunosuppression caused by Trypanosoma evansi infection and malnutrition in experimental buffaloes with skin sensitisation tests - Partoutomo, S (Indonesian Animal Sciences Society, 2000)
The main impacts of T. evansi infection in cattle and buffaloes include weight losses, deaths, and reduction of productivity, morover immunosuppressive conditions as a result of this parasite infection are commonly found. Dinitrochlorobenzene skin contact sensitisation (DNCB), phytohaemagglutinin skin (PHA) and homologous passive cutaneous anaphylaxis (HPCA) tests have been used for diagnosis of immunosuppression in man. The purposes of these experiments were to detect immunosuppression caused by T. evansi infection and malnutrition in normal and malnutrition buffaloes. Sixteen male and female buffaloes, 12-18 months of ages were divided into 4 groups, Group1 fed with high grade of ration and infected with T. evansi, Group2 fed with high grade of ration not infected, Group3 fed with low grade of ration and infected with T. evansi, and Group4 fed with low grade of ration and not infected. Buffaloes fed with high grade of ration are assumed as normal animals, while buffaloes fed with low grade of ration are assumed as malnutrion animals. These buffaloes were kept in fly proof fences in the Research Institute for Veterinary Science, Bogor. The experimental results indicated that normal buffaloes produced significantly (P<0,05) wider and thicker inflammation areas in DNCB and PHA test respectively than malnutrition and T. Evansi infected buffaloes one week after T. evansi infection. The widest skin reaction of 33 + 4.7 mm2 in DCCB and the thickest skin reaction of 45 + 1,0 in PHA test was obtained in 24 hours after DNCB challenge or PHA injection. Thereafter both DNCB and PHA test showed the reduction of the skin reactions, however they were still positive in 48 hours and becoming negative in 72 hours later. PHA test was able to differenciate the intensity of either the combined effects of malnutrition and T. evansi infection, T. evansi infection, or malnutrition alone. HPCA test showed inconsistent results. Â Keys words : Trypanosoma evansi, immunosuppression, DNCB, PHA, HPCA